Cytogenetic and agro-morphological study of Wheat addition lines possessing Thinopyrum elongatum and Aegilops triuncialis chromosomes - Devkota, Sushma; Maharjan, Raju; Pant, Deepak Raj; Joshi, Giri Prasad (Journal of Nepal Agricultural Research Council, 2023)
Novel genetic variation can be induced by introgression of alien chromosomes in wheat for which wheat-alien addition lines carrying 45 chromosomes are instrumental. In the course of developing wheat addition lines with 45 chromosomes, two different parental lines Wheat-Thinopyrum elongatum disomic addition lines (Wheat-Th. DALs; 2n=44)) and Wheat-Th. elongatum- Aegilops triuncialis 3CSAT double monosomic addition lines (Wheat-Th. DMALs; 2n=44) need to cross. The present study mainly focuses on the effects of chromosomal additions in wheat background by comparing the morphological and agronomic traits of the parental lines. Both the parental lines were reconfirmed 2n=44 cytologically by using squash technique. Pollen fertility was highest (75%) in Wheat-3CSAT-6E DMAL and lowest (44.73%) in Wheat-5E DAL, whereas, spike length was longest (8.71 cm) in Wheat-3CSAT-3E DMAL and shortest (5.92 cm) in Wheat-1E DAL. Plant height was highest (97.6 cm) in Wheat-3CSAT-5E DMAL and lowest (55.33 cm) in Wheat-7E DAL. The plant height of DMALs always exceeded that of DALs. Furthermore, seed set was highest (31 seeds per spike) in Wheat-7E DALs and lowest (13 seeds per spike) in addition lines disomic for 4E chromosomes. The effect of different alien chromosomes in wheat is discussed in this paper.